Prevalence and Associated Factors of Central Sensitization in Patients with Chronic Inflammatory Rheumatic Disease - Berrichi, Imane; Taik, Fatima Zahrae; Haddani, Fouzia; Soba, Nabil; Fourtassi, Maryam; Abourazzak, Fatima Ezzahra (Current Rheumatology Reviews, 2025)
ObjectiveDespite advances in the treatment of Chronic Inflammatory Rheumatic Disease (CIRD), pain remains a significant burden for patients and doctors. This study explored the prevalence and associated factors of central sensitization (CS) in patients with CIRD.MethodsThis is a cross-sectional study that included patients with CIRD followed at the University Hospital Center in Tangier. Sociodemographic and clinical data were collected. Nociceptive pain was assessed by the Visual Analogue Scale (VAS), disease activity by DAS-28 and ASDAS, and CS by the validated Moroccan version of the Central Sensitization Inventory part A (CSI-A). The Pain Catastrophizing Scale (PCS) was used to assess pain-related catastrophic thoughts, and the PHQ-9 (Pain Health Questionnaire) was used to determine the severity of depressive symptoms.ResultsWe included 189 patients; 107 (56.61%) had rheumatoid arthritis. The median duration of evolution of CIRD was 8 years, and the mean age was 47.49 ± 13.70 years, and 75.7% were women. The mean pain VAS was 4.77+-2.76, and 37.6% of patients were in remission. The mean central sensitization score was 37.42+- 16.75, with 44.9% having a CSI score ≥ 40. In univariate and multivariate analysis, our study showed that central sensitization is associated with pain severity (β = 1.945(0.050-1.916), p = 0.039) and depression (β = 1.790(1.221-2.154), p ≤ 0.001)(8). A statistically significant correlation was found between the CSI-A score and pain VAS (r = 0.32, p < 0.001).ConclusionOur study showed that almost half of our patients with CIRD had CS. The main factors associated with CS in our patients were pain severity and depression. We also found a significant correlation between pain VAS and CSI.
Keywords: pain